2019
DOI: 10.1007/s00270-019-02202-z
|View full text |Cite
|
Sign up to set email alerts
|

The pCONUS HPC: 30-Day and 180-Day In Vivo Biocompatibility Results

Abstract: Background Endovascular stents are commonly used during neurointerventional procedures; however, the concomitant use of dual anti-platelet treatment (DAPT) can limit their use. There is a need to develop stent coatings that mitigate requirement for DAPT. Methods The hydrophilic polymer coating is a novel glycan-based multilayer polymer that inhibits platelet adhesion. After Institutional Animal Care and Use Committee approval, 18 New Zealand white rabbits (mean weight 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…It is designed to mimic the biological properties of the glycocalyx, the coverage that can be found on the luminal surface of the endothelium of the arterial wall, making the coated surface hydrophilic and, consequently, less thrombogenic [4]. pHPC has no pharmaceutical effect, is biocompatible with no evidence of acute inflammatory response, and does not interact with the physical properties of the metallic implant [10,11]. Bhogal et al [5] recently reported on the use of the p48MW HPC under SAPT in treating five patients with unruptured aneurysms and reported no thromboembolic complications, with just one patient experiencing a minor hemorrhage from the treated aneurysm 2 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It is designed to mimic the biological properties of the glycocalyx, the coverage that can be found on the luminal surface of the endothelium of the arterial wall, making the coated surface hydrophilic and, consequently, less thrombogenic [4]. pHPC has no pharmaceutical effect, is biocompatible with no evidence of acute inflammatory response, and does not interact with the physical properties of the metallic implant [10,11]. Bhogal et al [5] recently reported on the use of the p48MW HPC under SAPT in treating five patients with unruptured aneurysms and reported no thromboembolic complications, with just one patient experiencing a minor hemorrhage from the treated aneurysm 2 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In November 2018, a coated variant of the p48MW obtained CE mark and has been made available for European patients. The HPC has been tested extensively in vitro and ex vivo, and the first clinical experiences have been reported (16)(17)(18)(19)(20)(21). Basically, the coating consists of a covalently bonded pentasaccharide layer at the surface of the device, which prevents platelet and leukocyte adhesion at the surface of the nitinol mesh.…”
Section: P48mw Vs P48mw Hydrophilic Coatingmentioning
confidence: 99%
“…It is designed to mimic the biological properties of the glycocalyx, the coverage that can be found on the luminal surface of the endothelium of the arterial wall, making the coated surface hydrophilic and, consequently, less thrombogenic 7. In vivo studies have shown that the pHPC has no pharmaceutical effect and is biocompatible in both dogs and rabbits, with no evidence of acute inflammatory response 27–29. These in vivo studies comparing coated and uncoated devices showed no difference in the rate of neo-endothelialization, which implies that pHPC reduces the thrombogenicity of the device but does not inhibit its endothelialization.…”
Section: Discussionmentioning
confidence: 99%